Tandem Schiff-Base Formation/Heterocyclization: An Approach to the Synthesis of Fused Pyrazolo–Pyrimidine/Isoxazolo-Pyrimidine Hybrids - Sambaiah, M.; Mallesham, Poosa; Shiva Kumar, K.; Bobde, Yamini; Hota, Prasanta Kumar; Yennam, Satyanarayana; Ghosh, Balaram; Behera, Manoranjan (Synlett, 2019)
A new synthesis of pyrazolo[4,3-d]pyrimidines and isoxazolo[4,5-d]pyrimidines is described. Key steps in the synthesis involve Stille coupling of 4,6-dichloro-2-phenyl-pyrimidine with tributyl(1-ethoxyvinyl)stannane and tandem Schiff-base formation/heterocyclization of 2,6-di-aryl-5-fluoro-4-acetylpyrimidine with hydrazines or hydroxylamine to give pyrazolo[4,3-d]pyrimidines and isoxazolo[4,5-d]pyrimidines, respectively. The position of the fluoro group in the pyrimidine ring is important for the success of heterocylization reaction.
Keywords: pyrazolo[4,3-d]pyrimidine; isoxazolo[4,5-d]pyrimidine; Stille coupling; Schiff base